Minimax Regret Estimation of Exponential Distribution Based on Record Values Under Weighted Square Error Loss Function - H. Zakerzadeh; M. Karimi (Journal of Mathematical Extension, 2014)
In this paper, we consider the problem of estimating the scale parameter of exponential distribution after preliminary test when the record values are available. The optimal significance levels based on the minimax regret criterion and the corresponding critical values are obtained. This estimator is illustrated by a numerical example.